SCIENTIFIC ANALYSIS OF THE EVOLUTION OF POLI TIMISOARA IN LEAGUE 1, 2013 -2014 - Stelescu Ioan (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2015)
The scope of the study was not to experiment but to explore and analyse the evolution of the team since I was directly involved in its training. Therefore, I was in direct daily contact with the members of the lot, realising numerous findings and observations during the return matches of the championship with every new method and training means proposed, and then I wanted to observe the real reasons which lead to the team's regression by the end of the competition season 2013-2014.